Comparative sequence analysis of nitrogen fixation-related genes in six legumes - Kim, Dong Hyun; Parupalli, Swathi; Azam, Sarwar; Lee, Suk-Ha; Varshney, Rajeev K. (Frontiers in Plant Science, 2013)
Legumes play an important role as food and forage crops in international agriculture especially in developing countries. Legumes have a unique biological process called nitrogen fixation (NF) by which they convert atmospheric nitrogen to ammonia. Although legume genomes have undergone polyploidization, duplication and divergence, NF-related genes, because of their essential functional role for legumes, might have remained conserved. To understand the relationship of divergence and evolutionary processes in legumes, this study analyzes orthologs and paralogs for selected 20 NF-related genes by using comparative genomic approaches in six legumes i.e. Medicago truncatula (Mt), Cicer arietinum, Lotus japonicus, Cajanus cajan (Cc), Phaseolus vulgaris (Pv) and Glycine max (Gm). Subsequently, sequence distances, numbers of synonymous substitutions per synonymous site (Ks) and nonsynonymous substitutions per nonsynonymous site (Ka) between orthologs and paralogs were calculated and compared across legumes. These analyses suggest the closest relationship between Gm and Cc and the farthest distance between Mt and Pv in 6 legumes. Ks proportional plots clearly showed ancient genome duplication in all legumes, whole genome duplication event in Gm and also speciation pattern in different legumes. This study also reported some interesting observations e.g. no peak at Ks 0.4 in Gm-Gm, location of two independent genes next to each other in Mt and low Ks values for outparalogs for three genes as compared to other 12 genes. In summary, this study underlines the importance of NF-related genes and provides important insights in genome organization and evolutionary aspects of six legume species analyzed.